Las bases históricas del «milagro de San Martín»: control territorial y estrategias estatales contra el narcotráfico y subversión (1980-1995) - Manrique López, Hernán (Pontificia Universidad Católica del Perú, 2015)
The present article demonstrates the historical bases previous to the success of alternative development in the region San Martín. It shows that anti-drug policy was unable to successfully function during the 1980s due to an absence of basic security conditions in the region. The ar- ticle’s main objective consists in presenting how the state managed to meet said security condi- tions. Thus, this article is divided into two periods of analysis. First, it focuses on the time period from 1980 to 1989 and shows how generalized state repression resulted counterproductive in the region because of strong subversive forces. Second, it presents the time period from 1989 to 1995 and demonstrates how the exercise of sequential period of focalized repression facilitated an environment to fight against drug trafficking. In this way, the focalized strategy and sequence permitted the state to resume security conditions that in a post-boom and post-conflict situation permitted the implementation of alternative development programs.

El presente artículo muestra las bases históricas previas al éxito del desarrollo alternativo en la región San Martín. Se muestra que la política antidrogas no pudo llevarse a cabo exito- samente durante la década de los ochenta debido a la ausencia de condiciones de seguridad mínimas en la región. De esta manera, el principal objetivo del artículo consiste en presentar cómo el Estado logró alcanzar dichas condiciones de seguridad. Para ello, la investigación se divide analíticamente en dos períodos. El primero se extiende de 1980 a 1989 y muestra cómo la ‘represión generalizada’ del Estado resultó contraproducente en la región debido a la presencia subversiva. El segundo parte de 1989 y se extiende hasta 1995 y muestra cómo, al ejercer una ‘represión focalizada’, de carácter secuencial primero en la subversión se facilitó el terreno para después luchar contra el narcotráfico. De esta manera, esta estrategia focalizada y secuencial permitió retomar las condiciones de seguridad que, en una situación post-boom y post-conflicto,facilitaron la implementación de los programas de desarrollo alternativo.
The historical basis of the «San Martín miracle»: territorial control and state strategies against drug trafficking and subversive organizations (1980-1995)
Keywords: Politics; Drug Trafficking; Subversion; Territorial Control; Alternative Development; Narcotráfico; Subversión; Control Territorial; Desarrollo Alternativo; https://purl.org/pe-repo/ocde/ford#5.06.00